Percutaneous Transluminal Coronary Angioplasty after Cardiac Transplantation - Avedissian, Michael G. (1989)
This report describes the 1st use of percutaneous transluminal coronary angioplasty in a posttransplant patient at the Texas Heart Institute. The patient, a 44-year-old man, experienced 3 episodes of moderate allograft rejection, hypercholesterolemia, transient severe hyperglycemia, and transient severe renal insufficiency in the posttransplant period. His cholesterol levels became elevated immediately and remained between 200 and 250 mg/dL, despite treatment with gemfibrozil. He had increasing lower-extremity claudication that was treated with bilateral femoral-popliteal bypass grafting. At 5-year follow-up, a discrete 75% stenosis was found in the right coronary artery. He was treated successfully with percutaneous transluminal coronary angioplasty on 20 February 1989 and was able to return to work thereafter. (Texas Heart Institute Journal 1989;16:288-91)